Exploring genetic variation and phylogenetic patterns of Tropilaelaps mercedesae (Mesostigmata: Laelapidae) populations in Asia - Mohamadzade Namin, Saeed; Joharchi, Omid; Aryal, Sunil; Thapa, Ratna; Kwon, Sun-Ho; Kakhramanov, Boymakhmat A.; Jung, Chuleui (Frontiers in Ecology and Evolution, 2024)
Introduction The mites belonging to the genus Tropilaelaps are ectoparasites of honey bees, primarily infesting the larval and pupal stages. Originating from subtropical regions, these mites can cause brood malformation, bee mortality, and subsequent decline or absconding of colonies. Material and methods During field surveys conducted in Nepal, South Korea, and Uzbekistan to investigate honey bee pests, several populations of T. mercedesae were collected. This is the first record of T. mercedesae from Uzbekistan. The morphological characteristics of the collected populations were analyzed, and their phylogenetic relationship with other Asian populations was examined. Results and discussion The molecular analysis of cytochrome oxidase I gene revealed high similarity between Uzbekistan and Pakistan populations, signaling the potential invasion of subtropical honey bee parasites into the Central Asian beekeeping sectors. Phylogenetic analysis indicated the presence of four distinct lineages within the mainland-Indonesian populations of T. mercedesae. Notably, an evolutionary divergence was observed between the haplotypes from Sri Lanka and the Philippines compared to the remaining mainland Asian and Indonesian haplotypes, suggesting the possible existence of subspecies or separate species in these isolated locations. To gain a deeper understanding of this phenomenon, it is essential to continue monitoring the spread of this significant honey bee pest and conduct comprehensive morphological and molecular analyses of samples collected from these specific localities.